Knowledge and practice of breast self examination among women of reproductive age in Butwal Sub Metropolitan City - Marahatta, S.B.; Sharma, S. (Journal of Manmohan Memorial Institute of Health Sciences, 2018)
Background: Majority of breast cancer cases in developing countries are diagnosed in late stage. Breast cancer is the second most common cancer among females in Nepal and can be detected by Breast self-examination (BSE) in early stage of disease. This study aimed to assess the knowledge and practice of breast self-examination among women of reproductive age in Butwal Sub-Metropolitan city. Methods: A quantitative descriptive cross-sectional study with 219 women of reproductive age residing in Butwal Sub-Metropolitan city was conducted between March and August 2016. The study samples were enrolled through the cluster random sampling design. Data was collected using an interviewer administered semi-structured questionnaire. Data was analyzed using SPSS ver. 16.Association was checked using the chi-square test. Results: Of total, only 31.1% of respondents had ever heard about BSE. Only 19.2% women had ever practiced BSE. The study revealed that marital status, monthly household income and level of education were independent factors influencing the knowledge of BSE while performance of BSE was influenced by monthly household income, level of education and history of breast disease. Conclusion: Knowledge and practice of BSE among women of reproductive age in Butwal sub metropolitan city was found poor and inadequate. This shows gap between knowledge and practice of BSE that might be reduced through implementation of community based awareness and skill development programs on BSE targeting the women of reproductive age group. JMMIHS.2018;4(1):117-129